2011
DOI: 10.1038/ki.2010.437
|View full text |Cite|
|
Sign up to set email alerts
|

De novo development of circulating anti-endothelial cell antibodies rather than pre-existing antibodies is associated with post-transplant allograft rejection

Abstract: Anti-endothelial cell antibodies (AECAs) are thought to be involved in the development of renal allograft rejection. To explore this further, we determine whether AECAs play a role both in predicting the incidence of allograft rejection and long-term outcomes by analysis of serum samples from 226 renal allograft recipients for AECAs pre- and post-transplant. Surprisingly, the presence of pre-existing AECAs was not associated with either an increased risk of rejection or a detrimental impact on recipient/graft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…Non-HLA antibodies, although potentially determinants of outcomes, are outside the scope of this review and will be discussed only briefly. [11][12][13][14] …”
mentioning
confidence: 99%
“…Non-HLA antibodies, although potentially determinants of outcomes, are outside the scope of this review and will be discussed only briefly. [11][12][13][14] …”
mentioning
confidence: 99%
“…Also, AMR can be caused by non-HLA antibodies. These may include hemagglutinin A or B antibody, anti-MICA, anti-minor histocompatibility antigens (MiHA), antiendothelial antibodies and anti-angiotensin-2 receptor [2] [17] [18]. As our knowledge in transplant immunology advances, there will likely be more alloreactive and autoreactive antibodies to be discovered in the future.…”
Section: Antibody-mediated Rejectionmentioning
confidence: 99%
“…A single center study demonstrated an association between de novo posttransplant anti-endothelial cell antibodies and recurrent transplant rejection resulting in allograft dysfunction [19]. The specific antigenic target remains to be determined.…”
Section: Antibodies To Non-hla Antigens and Transplant Outcomementioning
confidence: 99%